Material evidence and narrative sources : interdisciplinary studies of the history of the Muslim Middle East - Talmon-Heller, Daniella.; Cytryn-Silverman, Katia. (Islamic History and Civilization, 2014)
This book is a collected volume that crosses traditional boundaries between methodologies. Each of its sixteen articles is based on imaginative combinations of data provided by excavations, artifacts, monuments, urban topography, rural layouts, historical narratives and/or archival records. The volume as a whole demonstrates the effectiveness of interdisciplinary research applied to historical, cultural and archaeological problems. Its five sections - Economics and Trade , Governmental Authority , Material Culture , Changing Landscapes , and Monuments - bring forth original studies of the medieval, Ottoman and modern Middle East, amongst others, of voiceless and silenced social groups. Contributors are: Nitzan Amitai-Preiss, Jere L. Bacharach, Simonetta Calderini, Delia Cortese, Katia Cytryn-Silverman, Miriam Frenkel, Haim Goldfus, Hani Hamza, Stefan Heidemann, Miriam Kühn, Ayala Lester, Nimrod Luz, Yoram Meital, Daphna Sharef-Davidovich, Oren Shmueli, Yasser Tabbaa, Daniella Talmon-Heller, and Bethany Walker.